Experimental Study of the Effect of Preheating Process on Welded Joints of ASTM A36 Material on Mechanical Characteristics: Evaluation of Tensile, Bending, and Macrostructure - Irawan, Benny Haddli; Novian, Fazri Dwi Putra; Saihilmi, Muhammad Irsyad (Jurnal Teknologi, 2025)
In the oil and gas industry, welding errors frequently necessitate replating. Preheating is a heat treatment method used to minimize temperature gradients between the weld area and its surroundings, thereby reducing the risk of weld defects. This study employs an experimental approach to evaluate the effect of preheating during rewelding and to assess the resulting mechanical properties of the weld metal. The experiment involved two rewelding cycles with preheating. The minimum preheating temperature was set at 50 ºC, and the minimum interpass temperature at 240 ºC. Shielded Metal Arc Welding (SMAW) was used to weld ASTM A36 carbon steel. The experimental procedures included tensile testing, bending testing, and macrostructural analysis. Welding was performed on A36 steel using E7016 and E7018 filler materials, with a current of 94.1 A and a groove configuration featuring a 30º bevel angle. The findings of this research can inform the development or revision of procedure qualification records (PQR) to meet industry quality and safety standards.